Speech and language therapists' views on parents' engagement in Parent–Child Interaction Therapy (PCIT). Issue 4 (7th February 2019) - Klatte, Inge S.; Harding, Sam; Roulstone, Sue
Abstract: Background: Parents' play an essential role in Parent–Child Interaction Therapy (PCIT) as the primary agent of intervention with their child. Unfortunately, speech and language therapists (SLTs) report that parents' engagement is challenging when conducting PCIT. Although focusing on and stimulating the engagement of parents, when needed, can increase the success of PCIT, little is known about what factors influence parent engagement. Aims: To explore SLTs' views about the factors that facilitate or pose barriers to parents' engagement in PCIT. Methods & Procedures: A secondary analysis of 10 interview transcripts about SLTs' views on delivering PCIT with parents of children with developmental language disorder (DLD) was conducted. Codes from the original analysis where checked for their relevance to parents' engagement by the first author. Potential themes were identified iteratively with all authors. Outcomes & Results: Four themes were identified in the SLTs' description of their experiences with the engagement of parents: mutual understanding, creating a constructive relationship between the SLT and parent, parental empowerment, and barriers. It became clear that SLTs were focusing on different aspects of engagement. Conclusions & Implications: This study makes an initial contribution to our understanding of SLTs' view of parents' engagement and about what stimulates parent engagement or effects disengagement. SLTs play an important role in supporting parents to engage and stay engaged with therapy. Training SLTs on how best to engage parents, focusing on mutual understanding, creating constructive relationships between the SLT and parent, parental empowerment, and barriers, is necessary. However, more research is needed on how to train relevant skills in SLTs. Clearer definitions of engagement would improve understanding and judgements about how best to support parents.